Safety study of 38 503 intravitreal ranibizumab injections performed mainly by physicians in training and nurses in a hospital setting. (17th November 2014) - Hasler, Pascal W.; Brandi Bloch, Sara; Villumsen, Jørgen; Fuchs, Josefine; Lund‐Andersen, Henrik; Larsen, Michael
Abstract Purpose To evaluate and to compare the safety of intravitreal ranibizumab injections performed by physicians and nurses at a single large hospital clinic in Denmark during 5 years. Design Retrospective, interventional, non‐comparative study. Methods Setting: All eyes that underwent a protocolized ranibizumab injection procedure performed in an operating room mainly by nurses and physicians in their first year of ophthalmology training. Study population: A total of 4623 eyes in 3679 patients with subretinal neovascularization secondary to a variety of retinal diseases, mainly neovascular AMD treated with intravitreal therapy (IVT) at the Glostrup Hospital from January 1, 2007 to December 31, 2011 with a mean follow‐up of 12.2 months (95% confidence interval: 11.9–12.6). Main outcome measures: Frequency of endophthalmitis, traumatic cataract, intraocular haemorrhage and retinal detachment from 2007 to 2012. Results Overall, 38 503 intravitreal ranibizumab injections were performed in 4623 eyes. Injections were performed by nurses (32.5%), ophthalmology residents (61.3%) and vitreoretinal surgeons (6.2%). Severe complications to treatment were observed in 17 eyes: Endophthalmitis (14 eyes, 0.36 ‰ of injections whereof seven cases were culture‐positive), anterior uveitis (one eye, 0.026 ‰), traumatic cataract (one eye, 0.026 ‰) and rhegmatogenous retinal detachment (one eye, 0.026 ‰). Retinal pigment epithelial tears were registered in 14 eyes in 14 subjects within the first year of treatment with ranibizumab. Of the 14 cases of endophthalmitis, seven occurred within a period of 5 weeks in 2010 when occasionally abnormal needle outflow resistance prompted the needle replacement in the operating room. No drug‐related adverse events were recorded. Conclusions Intravitreal ranibizumab injection performed by nurses and physicians without preinjection topical antibiotics was associated with a rate of injection‐related adverse events of 0.44 ‰.